Vpliv oskrbe z energijo na sonaravno uravnotežen razvoj Slovenije v obdobju do leta 2020 - Žun, Štefan (Strojniški vestnik, 2004)
Knowing that humans overexaggerated extracting nonrenewable natural sources which caused nonequal quality of life lead to the awareness that energy and mass flows generated by mankind should be decreased drastically. Only than the sustainable development on the planet could be achieved. Slovenia also expresses commitment to the sustainable development. The grade approaching to the final goal can be measured only by an appropriate method. In the last years the environmental footprints become wide used. In the paper the method is described and first time used for calculation of environmental footprints of Slovenian inhabitance. It was found out that current development is non sustainable because environmental footprints of Slovenian's are greater than local and global bio-productive space. The influence of the current energy use on the environmental footprints is analyzed and prediction of the future environmental footprints caused by the use of energy predicted in most important national strategic documents and EU Directives up to year 2020 are presented.
Keywords: Slovenia; Slovenija; razvoj uravnotežen; oskrba z energijo; sledi ekološke; raba energije; natural environment; okolje; raziskave; planiranje